INTERCULTURAL COMMUNICATION AT HIGHER EDUCATION CONTEXT: PORTRAITS AND PRACTICES - Wello, Muhammad Basri (International Journal of Language Education, 2017)
Abstract : Intercultural communication focuses on the importance of understanding other?s language and cultural background in order to create effective communication. In terms of a subject studied at higher education setting, It is not only concern about mark and result of study but also about quality relationship between lecturers and students. This ideal situation appears to be unbridged well due to the practice of learning for examination. Several studies on effective learning have been conducted, these include  study about effective learning, how to create it and how it influenced by teaching pedagogy or other aspects such as those conducted in high school or at higher education settings. This article reviews several studies on intercultural competence from five different countries. The objective of this study is to present research from different context, models of intercultural communication developed in those settings and possible adaptive models to develop in higher education settings. Data were obtained from a careful review of international articles on the study of intercultural communication using inclusion and exclusion criteria. Result of the review reveals that intercultural communication is the effective pathway for developing teachers? intercultural sensitivity and professional identity, important aspects to teach in the lecture include emotional intelligence, personal competencies and social competencies that is relevant to future workforce. These studies also encourage lecturers to be curriculum developer rather than merely being curriculum implementer. Implications and suggestions for further study are also provided.